Radiographic patterns of osteoarthritis of the knee joint in the community: the importance of the patellofemoral joint. Issue 7 (July 1992) - McAlindon, T E; Snow, S; Cooper, C; Dieppe, P A
Abstract : The intimate relation which the patella has with the knee joint and quadriceps muscle suggests that patellofemoral joint osteoarthritis is likely to be an important cause of knee pain and disability. Two hundred and seventy three subjects who reported knee pain in a postal questionnaire survey and 240 control subjects consented to have anteroposterior weightbearing and lateral knee radiographs. Each subject completed a Stanford Health Assessment Questionnaire (HAQ). Radiographic knee osteoarthritis was found in 53% of symptomatic and 17% of asymptomatic subjects. Three patterns predominated patellofemoral, medial, and medial/patellofemoral joint disease in 11, 21, and 7% of the men and in 24, 12, 6% of the women respectively. The occurrence of isolated symptomatic patellofemoral joint osteoarthritis in this sample aged more than 55 years was estimated as 8% in women and 2% in men. All patterns of symptomatic knee joint osteoarthritis increased with age in women but peaked at 70 years in men. Medial joint and patellofemoral joint osteoarthritis were significantly associated with disability (46 v 17% in controls and 64 v 25% in controls respectively) but higher HAQ scores were more common in subjects with patellofemoral joint osteoarthritis. Patellofemoral joint osteoarthritis is common, associated with disability, occurs in the absence of tibiofemoral disease, and can no longer be omitted from future studies of osteoarthritis of the knee joint.